FACILITATING LGBTQIA+ ALLYSHIP THROUGH MULTIMODAL WRITING IN THE ELEMENTARY CLASSROOM preparing... teachers to challenge heteronormativity. - Dunkerly, Judith M.; Poplin, Julia Morris; Sledd Taylor, Valerie ([S.l.] : ROUTLEDGE, 2022)
This book reports findings of a qualitative study intended to disrupt notions of heteronormativity amongst preservice elementary teachers by engaging them in multimodal writing and text production around issues facing LGBTQIA+ youth. Against the backdrop of increasing anti-transgender sentiment in the United States, the text highlights the necessity of integrating queered pedagogy in teacher education to facilitate candidates' movement through the continuum and leave them prepared, equipped, and willing to support children identifying as LGBTQIA+. Through analysis of picture books, infographics, and multimodal texts produced by teacher candidates, this cutting-edge volume develops a continuum of engagement, from apathy through to active allyship, with LGBTQIA+ youth. This timely volume will benefit researchers, academics, and educators with an interest in gender and sexuality studies, primary and elementary education, as well as teacher education more specifically. Those involved with queer theory and the sociology of education will also benefit from this volume.
Keywords: EDUCATION / Multicultural Education; Critical pedagogy; Heterosexism in schools